Auditors' Report and Financial Statements: For 6 month period ended 30 June 2008 - S. F. Ahmed & Co., Chartered Accountants (S. F. Ahmed & Co., Chartered Accountants, 2013)
Auditors' Report and Financial Statements for the period from 1st January 2008 to 30th June 2008.